Pyridoxine-dependent seizures in Dutch patients: diagnosis by elevated urinary alpha-aminoadipic semialdehyde levels. Issue 8 (6th November 2006) - Bok, Levinus A; Struys, Eduard; Willemsen, Michel A A P; Been, Jasper V; Jakobs, Cornelis
Abstract : Background: Pyridoxine-dependent seizures (PDS) is a rare, autosomal recessively inherited disorder. Recently α-aminoadipic semialdehyde (α-AASA) dehydrogenase deficiency was identified as a major cause of PDS, which causes accumulation of both α-AASA and pipecolic acid (PA) in body fluids. Methods: We studied urinary and plasma α-AASA and PA levels in 12 Dutch clinically diagnosed patients with PDS. Results: α-AASA was elevated in both urine and plasma in 10 patients. In these patients plasma PA levels were also elevated but urinary PA levels were normal. Discussion: In all patients with clinically definite PDS, and in most patients with probable or possible PDS, the clinical diagnosis of PDS could be confirmed at the metabolite level. Non-invasive urinary screening for α-AASA accumulation provides a reliable tool to diagnose PDS and can save these patients from the classical and potentially dangerous pyridoxine withdrawal test to prove PDS.